Model Pembelajaran dan Implementasi Posyandu Integrasi Layanan Primer (Studi Kasus) - Erma Pranawati; Supatmi; Eni Purwaningsih (Jurnal Riset Daerah, 2025)
The implementation of the Integrated Primary Health Care Post (ILP Posyandu) as a community-based integrated health service model still faces various challenges, particularly regarding the limited competencies of health cadres, inadequate facilities and infrastructure, and suboptimal reporting systems. As the frontline agents of Posyandu activities, cadres are required to integrate multiple sources of health information, conduct education sessions, manage data recording and reporting, and coordinate referral systems with puskesmas. Preliminary evaluations indicate that the competencies of Posyandu Gunung Krakatau cadres have not yet fully met the ILP implementation standards as stipulated in national regulations. This study aimed to analyze the effectiveness of three learning models classical, small group, and role-play in improving the knowledge and skills of Posyandu Gunung Krakatau cadres as preparation for implementing the Integrated Primary Health Care Post (ILP) based on local wisdom. This research employed a descriptive case study approach involving 16 Posyandu cadres in Soka Hamlet, Seloharjo, Pundong, Bantul. The program was conducted over three months (August–October 2025) through three learning phases: (1) the classical model to strengthen conceptual understanding, (2) the small group model to enhance technical skills, and (3) the role-play model to apply experiential learning through simulated real-life situations. Data were collected using pre-test and post-test assessments at each stage to measure changes in cadres’ knowledge and skills. The findings revealed significant improvements across all learning models. In the classical model, cadres with “good” knowledge increased from 18.75% to 62.5%. In the small group model, cadres with “good” skills increased from 18.75% to 68.75%. In the role-play model and direct ILP practice, cadres with “good” combined knowledge and skills rose from 31.25% to 87.5%. The role-play method proved to be the most effective, as it integrates theoretical learning with realistic practice in simulated community health settings. The combination of the three learning model classical, small group, and role-play was proven effective in improving the competencies of Posyandu cadres for the implementation of ILP based on local wisdom. The sequential and experiential learning approach created an interactive and practical learning process, strengthening cadres’ abilities in education delivery, basic health services, data management, and community referral systems. Continuous support from puskesmas, local governments, and community institutions is essential to provide regular training, adequate facilities, and digital reporting systems to ensure the sustainability of ILP Posyandu services at the community level.